2016
DOI: 10.1093/pm/pnw262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tanezumab on Osteoarthritis Knee and Hip Pains: A Meta-Analysis of Randomized Controlled Trials

Abstract: Tanezumab vs placebo provides superior pain relief and improvement in physical function and PGA in knee and hip osteoarthritis patients and is generally well tolerated with acceptable AEs. Low-dose tanezumab (10 or 25 µg/kg and 2.5 mg) provides similar effectiveness in reducing pain and improving function and is associated with fewer AEs. The long-term safety of tanezumab on osteoarthritis knee and hip pain needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…However, the FDA lifted its hold in March 2015, and in 2017 granted fast-track status as a nonopioid pain medication, 180 particularly for hip and knee osteoarthritis. 181 In the only reported study in DPN, 20 mg of SC tanezumab was administered on day 1 and week 8 and showed a reduction in DPN pain but no improvement in patients' global assessment of pain. 182 Vitamin D deficiency is associated with paresthesia and parasympathetic dysfunction 183,184 and is highly prevalent in diabetic populations.…”
Section: Intravenous Lidocainementioning
confidence: 96%
“…However, the FDA lifted its hold in March 2015, and in 2017 granted fast-track status as a nonopioid pain medication, 180 particularly for hip and knee osteoarthritis. 181 In the only reported study in DPN, 20 mg of SC tanezumab was administered on day 1 and week 8 and showed a reduction in DPN pain but no improvement in patients' global assessment of pain. 182 Vitamin D deficiency is associated with paresthesia and parasympathetic dysfunction 183,184 and is highly prevalent in diabetic populations.…”
Section: Intravenous Lidocainementioning
confidence: 96%
“…In the past two years, several systematic reviews (1315) have concluded that, compared to placebo, blockade of NGF with targeted monoclonal antibodies yielded substantial improvement in pain and in function. Tanezumab, used at doses of 5 mg and 10 mg, was statistically significantly superior to the active comparators, NSAIDs or opiates, with standardized effect sizes of 0.22 to 0.24 (13, 16).…”
mentioning
confidence: 99%
“…Tanezumab, used at doses of 5 mg and 10 mg, was statistically significantly superior to the active comparators, NSAIDs or opiates, with standardized effect sizes of 0.22 to 0.24 (13, 16). Chen et al reported that low dose (≤2.5mg) tanuzemab treatment had comparable efficacy to high dose, but with significantly fewer adverse effects (15). Since then, development of higher dose anti-NGF has ceased.…”
mentioning
confidence: 99%
“…102 Currently, no DMOADs have been licensed for use in the treatment of OA, but several putative DMOADs are in phase II development. In particular, monoclonal antibodies (mAbs) and inhibitors directed against OA-related cytokines, such as tumor necrosis factor α (TNF-α), [103][104][105][106] nerve growth factor, [107][108][109] or interleukin molecules like IL-1α/β, [110][111][112] are under investigation, due to their regular use as biological disease-modifying antirheumatic drugs (bDMARDs) for the management of rheumatoid arthritis inflammation. 113 In a report comparing safety outcomes of bDMARDs in rheumatoid arthritis in 42 observational studies, a general safety profile of bDMARDs emerged with very sporadic cases of cardiovascular and infection incidence.…”
Section: Monoclonalmentioning
confidence: 99%